2021
DOI: 10.1177/03331024211010304
|View full text |Cite
|
Sign up to set email alerts
|

Photophobia and allodynia in persistent post-traumatic headache are associated with higher disease burden

Abstract: Objective To assess photophobia and allodynia in subjects with post-traumatic headache and examine how these sensory hypersensitivities associate with clinical measures of disease burden. Background Post-traumatic headache is the most frequent and disabling long-term consequence of mild traumatic brain injury. There is evidence of sensory dysfunction in acute post-traumatic headache, and it is known from other headache conditions that sensory amplifications correlate with more severe disease. However, systemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 40 publications
2
14
0
1
Order By: Relevance
“…In migraine, there is evidence of not only abnormal unimodal sensory processing, but also abnormal multimodal sensory processing with studies demonstrating that exposure to bright light reduces pain thresholds and trigeminal pain reduces visual discomfort thresholds 34,35 . Although reduced pain thresholds have been described in participants with PTH, 8,11–13 suggesting the presence of abnormal unimodal sensory processing, there are limited reports of abnormal multimodal sensory processing in participants with PTH. In a recent study, greater than 50% of the cohort with persistent PTH demonstrated both light and tactile hypersensitivity and demonstrate an interaction between the two sensory modalities (e.g., correlation between light and tactile hypersensitivity, and correlation between sensory hypersensitivities and disease burden) 8 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In migraine, there is evidence of not only abnormal unimodal sensory processing, but also abnormal multimodal sensory processing with studies demonstrating that exposure to bright light reduces pain thresholds and trigeminal pain reduces visual discomfort thresholds 34,35 . Although reduced pain thresholds have been described in participants with PTH, 8,11–13 suggesting the presence of abnormal unimodal sensory processing, there are limited reports of abnormal multimodal sensory processing in participants with PTH. In a recent study, greater than 50% of the cohort with persistent PTH demonstrated both light and tactile hypersensitivity and demonstrate an interaction between the two sensory modalities (e.g., correlation between light and tactile hypersensitivity, and correlation between sensory hypersensitivities and disease burden) 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Differences in sensory thresholds may differentiate the various phenotypes (migraine‐like vs. tension‐type‐like headache) in people with PTH 11 . Participants with PTH with multiple sensory sensitivities and lower sensory thresholds across multiple modalities, for example, light and tactile hypersensitivity, have a significantly higher headache frequency compared with those with a single or no hypersensitivity 8 . This suggests that hypersensitivity across sensory modalities may be a marker of disease severity.…”
Section: Introductionmentioning
confidence: 99%
“…The authors speculated that this association might suggest a potential migraine biology underlying the vestibular and balance dysfunction following concussion [33]. Allodynia has been reported in an estimated 35% of military members with PTH and 42-46% of civilians with PTH [34][35][36], leading to the hypothesis that mTBI may increase the risk for allodynia [37,38] and CM through altered descending modulation of trigeminal sensory processing [39]. The estimated frequency of allodynia among people with migraine is perhaps more variable (15.1% to 69.7%) [40], largely depending on chronicity, with a higher prevalence in CM than in episodic migraine patients [41,42].…”
Section: Remote Effect Of Mtbi On Migrainementioning
confidence: 99%
“…Finally, persistent PTH is associated with cutaneous allodynia and may be associated with cognitive impairment. Patients with persistent PTH have symptoms of sensory hypersensitivity and lower sensory thresholds with quantitative testing 39,40,51 . Although only 6% of patients in our study had a PTH diagnosis, approximately 25% of patients stated that they had a new headache or had their previous headache worsen within 7 days of the head injury, indicating that the proportion of patients with PTH might actually be higher.…”
Section: Discussionmentioning
confidence: 58%
“…Patients with persistent PTH have symptoms of sensory hypersensitivity and lower sensory thresholds with quantitative testing. 39,40,51 Although only 6% of patients in our study had a PTH diagnosis, approximately 25% of patients stated that they had a new headache or had their previous headache worsen within 7 days of the head injury, indicating that the proportion of patients with PTH might actually be higher. It is possible that the additive effects of pre-existing headaches and PTH result in greater symptoms of allodynia in the PEH(+) group.…”
Section: Discussionmentioning
confidence: 63%